Captain Underpants and the Big, Bad Battle of the Bionic Booger Boy, Part 1 : The Night of the Nasty Nostril Nuggets : Captain Underpants #6 - Pilkey, Dav, 1966- (New York : Blue Sky Press, 2003)
A snotty situation ensues when Melvin Sneedley, an academically gifted student, turns into the Bionic Booger Boy and must be stopped by George, Harold, and Captain Underpants.
Keywords: School principals -- Fiction; Schools -- Fiction; Heroes -- Fiction; Humorous fiction